Hexaaquamagnesium(II) bis{5-[3-(1H-tetrazol-5-yl)phenyl]tetrazolide} tetrahydrate - Qiao, Cheng-Fang (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, [Mg(H(2)O)(6)](C(8)H(5)N(8))(2)·4H(2)O, contains one half of the centrosymmetric dication, one anion and two water molecules. The Mg(II) ion is coordinated by six water molecules in a slightly distorted octahedral geometry. In the anion, the two five-membered heterocycles are twisted from the central benzene ring by 4.34 (11) and 3.20 (10)°. In the crystal, O—H⋯N, O—H⋯O and N—H⋯O hydrogen bonds generate a three-dimensional network.